Bezafibrate Exerts Neuroprotective Effects in a Rat Model of Sporadic Alzheimer's Disease - Li-Fan Lin; Yun-Ting Jhao; Chuang-Hsin Chiu; Lu-Han Sun; Ta-Kai Chou; Chyng-Yann Shiue; Cheng-Yi Cheng; Kuo-Hsing Ma (MDPI AG, 2022)
Bezafibrate, a pan-peroxisome proliferator-activated receptor (PPAR) agonist, reportedly attenuated tau pathology in a transgenic mouse model of primary tauopathy. Since tau pathology is a neuropathological hallmark of Alzheimer's disease (AD), bezafibrate may be a potential drug for the treatment of AD. However, no study has investigated its effects in AD models. Thus, we aimed to evaluate whether bezafibrate has neuroprotective effects in a sporadic AD model induced by streptozotocin (STZ) intracerebroventricular (ICV) injection. Rats were administered STZ-ICV (3 mg/kg) followed by bezafibrate (50 mg/kg/day, intraperitoneal) for 4 weeks. Behavior tests and positron emission tomography (PET) were performed to evaluate longitudinal changes in cognitive function, tau pathology, and cerebral glucose metabolism. Immunofluorescence staining was performed to assess neuronal survival and microglial accumulation. STZ-ICV administration induced significant cognitive impairment and substantial neuronal loss, tau pathology, glucose hypometabolism, and microgliosis in the cortex and hippocampus, while bezafibrate effectively attenuated these abnormalities. This study demonstrated that bezafibrate has long-lasting neuroprotective effects in a sporadic AD model. Our data indicate that the neuroprotective effects of bezafibrate might be associated with its ability to ameliorate tau pathology, brain glucose hypometabolism, and neuroinflammation. These findings suggest that bezafibrate is a potential multi-target drug candidate for the treatment of AD.